Keanekaragaman Kupu-Kupu Di Kawasan Air Terjun Dlundung Trawas, Kabupaten Mojokerto Jawa Timur Indonesia - Siti Zulaikha; Lu'luil Fajriyatil Aliyah (BioEksakta : Jurnal Ilmiah Biologi Unsoed, 2021)
The purpose of this study is to find out the diversity of butterflies in the area of Dlundung Trawas Waterfall, Mojokerto, East Java. The embedding method uses Visual Day Flaying by following the path in the area, the data obtained from observations are analyzed using the analysis of diversity index and Relative Abundance. Obtained as many as 22 species with a value of H'= 2.61 and the highest species FR are Libythea myrrha, Letopsia nina, Taencia palguna, and Papilio memnon. Based on these results it is known that the diversity of butterflies in the region in the moderate category due to the support of biotic and abiotic factors.